Analysis of Strain Criminology Theory on Perpetrators of Falsification of Population Administration Documents in Accordance with Law Number 23 of 2006 - Aruan, Yulia Christy Shintara; Ramadani, Suci; Rahmayanti , Rahmayanti (PT. Publikasiku Academic Solution, 2025)
The falsification of population administration documents is a form of crime that has serious implications for state administrative order and legal protection of society. This phenomenon can be analyzed through the strain criminology theory, which emphasizes social, economic, and structural pressures that drive individuals to commit deviant acts. This study aims to analyze the motives and driving factors of perpetrators of falsification of population administration documents using the perspective of strain theory, and to examine its relevance within the framework of Indonesian positive law, particularly Law Number 23 of 2006 on Population Administration. The research method used is normative juridical, by examining statutory regulations, criminological literature, and legal doctrines. The analysis shows that falsification of population documents is generally driven by economic pressure, limited access to administrative services, and certain social needs that cannot be fulfilled legally. From the strain perspective, these conditions generate tension that drives perpetrators to seek shortcuts through falsification. Meanwhile, Law Number 23 of 2006 explicitly regulates prohibitions and criminal sanctions against the falsification of population documents, although its enforcement still faces obstacles in prevention and law enforcement. Therefore, synergy between criminological and juridical approaches is needed to address this crime, namely by strengthening population administrative services, increasing legal awareness among society, and implementing both penal and non-penal policies in a balanced manner.